1997
DOI: 10.1084/jem.185.9.1573
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Tumor Necrosis Factor Alters T Cell Responses by Attenuating T Cell Receptor Signaling

Abstract: Repeated injections of adult mice with recombinant murine TNF prolong the survival of NZB/W F1 mice, and suppress type I insulin-dependent diabetes mellitus (IDDM) in nonobese diabetic (NOD) mice. To determine whether repeated TNF injections suppress T cell function in adult mice, we studied the responses of influenza hemagglutinin-specific T cells derived from T cell receptor (HNT-TCR) transgenic mice. Treatment of adult mice with murine TNF for 3 wk suppressed a broad range of T cell responses, including pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
200
2
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 274 publications
(226 citation statements)
references
References 39 publications
20
200
2
4
Order By: Relevance
“…A protective anti-inflammatory effect of TNF has also been described for the murine nonobese diabetes model (9). With the use of an influenza hemagglutinin transgenic T-cell receptor mouse model, TNF has been shown to suppress a broad range of T-cell responses, including IFN-␥ production (9). This in vivo observation of the IFN-␥-attenuating attribute of TNF was recapitulated in an in vitro model of chronic TNF exposure (9).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…A protective anti-inflammatory effect of TNF has also been described for the murine nonobese diabetes model (9). With the use of an influenza hemagglutinin transgenic T-cell receptor mouse model, TNF has been shown to suppress a broad range of T-cell responses, including IFN-␥ production (9). This in vivo observation of the IFN-␥-attenuating attribute of TNF was recapitulated in an in vitro model of chronic TNF exposure (9).…”
Section: Resultsmentioning
confidence: 85%
“…In addition, it has been reported that TNF mediates a tissue-damaging effect in the acute phase of inflammation in the mouse experimental allergic encephalomyelitis model while exerting an immunosuppressive effect as the disease progresses, which eventually leads to protection against tissue damage and remission (18,19). A protective anti-inflammatory effect of TNF has also been described for the murine nonobese diabetes model (9). With the use of an influenza hemagglutinin transgenic T-cell receptor mouse model, TNF has been shown to suppress a broad range of T-cell responses, including IFN-␥ production (9).…”
Section: Resultsmentioning
confidence: 92%
“…In healthy individuals these cells may have a role in preserving natural immune homeostasis, a function that is suppressed in RA (42). However, so far, the presence of functional HC gp-39-specific T cells in SF has been difficult to detect, possibly due to local T cell exhaustion or suppression (37)(38)(39)(40)42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of T cells to TNF, in particular during chronic inflammatory conditions, has been reported to exert antiinflammatory effects on T cells, in particular by attenuating TCRmediated signaling and proliferative expansion [13]. Prolonged exposure to TNF in vitro leads to hyporesponsiveness of T cells [14] possibly by uncoupling proximal [15] as well as distal [16] TCR signals, thus indicating an important and direct immunomodulatory function of TNF on activated T cells.…”
Section: Introductionmentioning
confidence: 99%